2020
DOI: 10.2516/ogst/2020032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a modified nano clay and nano graphene on rheology, stability of water-in-oil emulsion, and filtration control ability of oil-based drilling fluids: a comparative experimental approach

Abstract: During the past decade, researchers have used different Nano-Particles (NPs) due to their unique characteristics for improving formulation of Oil-Based Drilling Fluids (OBDFs). This study is the first research that investigates the effect of a Modified Nano Clay (MNC), namely CLOISITE 5 and non-functionalized Nano Graphene (NG) on rheology, electrical/emulsion stability, and filtration control ability, as the main properties of OBDFs. Initially, five concentrations of both NPs (0.25, 0.5, 1, 1.5, and 2 wt%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The Bingham plastic model is used to describe the rheological behavior of the two drilling fluid samples with R 2 values of 0.9773 (Claytone-IMG 400) and 0.9803 (MC-TONE). Several studies have provided support for the applicability of the Bingham plastic model in characterizing the flow properties of OBDFs 10 , 15 , 56 , 60 . Werner et al 56 demonstrated the effectiveness of the Bingham plastic model in capturing the viscoelastic properties and flow behavior of OBDFs, particularly under HPHT conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The Bingham plastic model is used to describe the rheological behavior of the two drilling fluid samples with R 2 values of 0.9773 (Claytone-IMG 400) and 0.9803 (MC-TONE). Several studies have provided support for the applicability of the Bingham plastic model in characterizing the flow properties of OBDFs 10 , 15 , 56 , 60 . Werner et al 56 demonstrated the effectiveness of the Bingham plastic model in capturing the viscoelastic properties and flow behavior of OBDFs, particularly under HPHT conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The best nanofluids for regulating filtration into formation were those containing modified nanoclay and nanographene, which had ∼32 % and ∼43 % smaller filtrate volumes than the base fluid, respectively. Furthermore, modified nanoclay can support fluid commercial loss control agents and emulsifiers to improve the formulation of the oil‐based drilling fluids, although its use is restricted because of the nanoparticles detrimental impact on emulsion stability [125] . In another work, nano enhanced WBDF were generated employing the synthesized ZnTiO 3 nanomaterials in a solution as a base fluid, which was then employed as an additive.…”
Section: Overview Of the Characteristics Of Different Nanomaterials I...mentioning
confidence: 99%
“…Furthermore, modified nanoclay can support fluid commercial loss control agents and emulsifiers to improve the formulation of the oilbased drilling fluids, although its use is restricted because of the nanoparticles detrimental impact on emulsion stability. [125] In another work, nano enhanced WBDF were generated employing the synthesized ZnTiO 3 nanomaterials in a solution as a base fluid, which was then employed as an additive. It was proven that the inclusion of one 1 wt% ZnTiO 3 nanomaterial to drilling fluid reduced the volume of fluid loss by around ∼ 8 %.…”
Section: Overview Of the Characteristics Of Different Nanomaterials I...mentioning
confidence: 99%
“…Conventional oil-based drilling fluids typically have high emulsion stability and strong oil-wetting properties, which render contact drilling pipes, formation, and drill cuttings oil-wet (Nooripoor and Hashemi, 2020). In drilling procedures, strong oil-wetting properties are beneficial for improving shale formation stability and reducing downhole accidents.…”
Section: Introductionmentioning
confidence: 99%